Pregabalin Abuse in Combination With Other Drugs: Monitoring Among Methadone Patients - Lancia, Massimo; Gambelunghe, Angela; Gili, Alessio; Bacci, Mauro; Aroni, Kyriaki; Gambelunghe, Cristiana (Frontiers in Psychiatry, 2020)
In recent years, there has been an increase in the non-medical use of psychoactive prescription drugs including pregabalin (PGB). Studies have shown that multiple drug users and patients in methadone treatment programs administered PGB at high dosages in order to achieve euphoria, reduce withdrawal symptoms, or potentiate the effects of methadone. For these reasons, accurate toxicological monitoring is required for these high-risk individuals. The present study investigated whether PGB could be detected in the hair samples of 250 patients with a history of opiate dependency, and under toxicological surveillance assess their compliance with methadone maintenance therapy. Opiates were found in 54/250 of all hair samples, while cannabis was present in 74/250 patients, cocaine was detected in 21/250 patients, and benzodiazepines without prescription were identified in 49/250 patients. As expected, methadone was present in all 250 patients (100%). PGB without prescription was found in the hair samples of 35/250 patients (14%). Of these, 91.43% were male, 48.57% were < 30 y old, and 45.71% were between ages 30 and 50 y. There were no apparent associations among PGB use, daily methadone dosage, and duration of methadone maintenance therapy. Psychiatric comorbidities were present in 25.71% of the patients abusing PGB. Anxiety (55.56%) and depression (33.33%) were the most prevalent psychiatric disorders. Most of the patients taking PGB (57.14%) used other drugs (especially opiates) concurrently. The utility of hair analysis is explained by easy and rapid sample collection and the ability of the hair to reflect long-term drug use and incorporate drug metabolites. The findings of this study suggested that PGB has significant potential for abuse by high-risk populations such as opioid users and patients with dual diagnosis. These risks are particularly high in cases of poly-drug use and drug intake that are not in compliance with prescription guidelines.